Altered Functional Connectivity in a Triple-Network Model in Autism With Co-occurring Attention Deficit Hyperactivity Disorder - Wang, Kai; Li, Ke; Niu, Xiaoyu (Frontiers in Psychiatry, 2021)
Purpose: This study aimed to explore alterations of functional connectivity (FC) within and between default mode network (DMN), executive central network (ECN) and salience network (SN)) in autistic spectrum disorder (ASD) with cooccurring attention deficit hyperactivity disorder (ADHD). Method: 135 individuals’ date of the Autism Brain Imaging Data Exchange Ⅱ (ABIDE Ⅱ) was used to compare the within-network and between-network connectivity of 45 ASD+ADHD with 45 ASD patients, then the correlation analysis between abnormal FC and behavior were performed. Results: The ASD+ ADHD group exhibited decreased within-network connectivity in the precuneus of ventral DMN and increased between-network connectivity between ventral DMN and dorsal DMN as well as ventral DMN and left ECN comparing with the ASD group. Besides, the strength of the abnormal between-network connectivity was related to the severity of autistic features. Conclusion: The dysfunction of DMN in the ‘triple-network model’ is the core evidence in ASD with cooccurring ADHD.